Hormonal and metabolic disorders in connective tissue dysplasia - I. D. Bespalova; Z. S. Chomaeva; A. V. Teteneva; Yu. I. Koshchavtseva; U. M. Mitrichenko; D. S. Romanov; S. V. Nesterovich; D. V. Poljakova; E. B. Bukreeva; T. V. Sorokina; E. V. Kalyuzhina; K. F. Tetenev; et al. (Бюллетень сибирской медицины)
The lecture considers the results of research conducted by Russian and foreign scientists concerning the characteristics of all types of metabolic disorders and hormonal imbalance in undifferentiated connective tissue dysplasia (CTD). Understanding the role of hormonal and metabolic disorders in the development and course of diseases associated with CTD is of great importance for the development of pathogenetically grounded algorithms for the diagnosis, treatment, and prevention of emergency conditions.